DEVELOPMENT OF DIGITAL LITERACY-BASED LEARNING INNOVATIONS IN THE SECOND SEMESTER OF THE INDONESIAN LANGUAGE AND LITERATURE COURSE AT THE UNIVERSITY OF NIAS IN THE ERA OF INDEPENDENT LEARNING: PENGEMBANGAN INOVASI PEMBELAJARAN BERBASIS LITERASI DIGITAL DALAM MATA KULIAH BAHASA DAN SASTRA INDONESIA SEMESTER II DI UNIVERSITAS NIAS PADA ERA MERDEKA BELAJAR - Riana Riana (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study investigates the development of digital literacy-based learning innovations within the second-semester courses of Indonesian Language and Literature at Universitas Nias, situated within the broader framework of the Merdeka Belajar (Freedom to Learn) policy. The research is grounded in the growing urgency for higher education institutions to adapt pedagogical strategies to the digital transformation era, particularly in remote or under-resourced regions. The central research question explores how the integration of digital literacy enhances the effectiveness and engagement of students in language and literature learning. Utilizing a qualitative descriptive approach, data were collected through classroom observations, interviews with lecturers and students, and documentation of learning media. The findings reveal that implementing digital tools—such as interactive e-modules, virtual discussion forums, and digital storytelling platforms—not only increases students’ motivation and participation but also fosters critical thinking and creative expression. However, challenges such as limited infrastructure and digital competencies among both students and lecturers persist. The study concludes that while the integration of digital literacy into the curriculum presents significant opportunities for pedagogical renewal, it requires continuous support in terms of technological access and capacity building. This research contributes to the discourse on localized innovations in Indonesian higher education and underscores the relevance of context-sensitive strategies in implementing national education policies.